Clinico-otoneurological assessment of the early postoperative outcome in surgical treatment of Chiari malformation and syringomyelia - Levchenyuk , Sofia; Derkach , Yuriy (The Ukrainian Scientific Medical Youth Journal, 2023)
although the pathology of Chiari malformation is extensively studied, many questions have not yet been solved. In particular, the clinical manifestations of this pathology have not been studied in detail entailing the lack of the unified approach for the optimal complex of the diagnostic workup and the selection of the optimal surgical intervention. These questions remain the point of discussion in the scientific literature. The present study is based on the retrospective analysis of the diagnostic findings and treatment outcomes of 59 patients – 24 males (40.7 %) and 35 females (59.3 %) – treated in the Department of spinal cord pathology of the State Institution "Romodanov Neurosurgery Institute, the National Academy of Medical Sciences of Ukraine" in 2010-2020. The age of the patients ranged from 16 to 50 years (36.9 ± 3.7 on the average). All patients were examined according to the conventional standards allowing for the assessment of the pre- and postoperative disease course. The following surgical interventions were provided: bone decompression for the inferior parts of the cerebellum at the upper cervical level; the recovery of the CSF flow at the region of craniovertebral junction; the expansion of the space in the fossa cranii posterior and/or craniovertebral junction. The data were processed and analyzed with the aid of STATISTICA 13 software. The quantitative variables were compared by non-parametric methods. The aim of the study was to analyze the preoperative and early postoperative clinico-otoneurological status in patients with Chiari malformation and syringomyelia. The clinical aspects of the disease were evaluated. Most clinical signs and symptoms in patients with Chiari malformation were associated with otolaryngological disturbances (hearing impairment, tinnitus, hoarseness, vertigo, etc.) and cerebellar signs (ataxia, nystagmus). Taking into account non-specific signs and symptoms of the disease, the otoneurological evaluation in these patients is undoubtedly of high importance for the preoperative differential diagnosis as well as the postoperative assessment of treatment outcome. The further study of the problem will allow us to timely diagnose Chiari malformation, to predict the course of the disease and the risk of the possible complications providing the clinicians with important information for decision-making on the optimal treatment strategy. The clinical and instrumental otoneurological examination is an important component of the systemic assessment of the clinical-and-functional status of patients with syringomyelia caused by Chiari malformation that allows for objectifying the dynamics of the otoneurological aspects of the disease in the course of the treatment.